Factors Associated with the Incidence of Underweight (Below the Red Line/BGM) Among Toddlers in Sumber Makmur Village, Tenggulun District, Aceh Tamiang Regency - Irma Nurianti; Amanda Putri (JURNAL KESMAS DAN GIZI (JKG), 2026)
Health development is a crucial component of national development aimed at improving the quality of human resources to become healthier, more intelligent, and more productive. One of the key indicators of successful health development is the reduction in infant and under-five mortality rates. Children under five years old are considered a vulnerable group due to their high risk of experiencing nutritional problems and diseases. Nutritional disorders in toddlers can increase susceptibility to infections, hinder growth and development, and reduce immune function and cognitive ability.  Underweight below the red line (BGM) is a condition of severe malnutrition resulting from inadequate intake of energy and protein over a relatively long period. In 2024, there were 11 recorded cases of BGM in Sumber Makmur Village. This study aims to identify factors associated with the incidence of BGM among toddlers. The study employed an analytical survey with a cross-sectional design, involving 72 toddlers selected through a simple random sampling technique. Data were collected through interviews and observations and analyzed using the Chi-Square test.  The results showed a significant relationship between exclusive breastfeeding and the incidence of BGM among toddlers (p=0.010), between nutritional knowledge and BGM (p=0.031), between husband’s income and BGM (p=0.018), and between the number of family members and BGM (p=0.001). Based on these findings, it is expected that mothers with toddlers experiencing BGM will improve their understanding of balanced nutrition, adopt regular feeding practices, and provide appropriate complementary foods according to the child’s age, and consistently apply these practices in daily life.